Fundamental orthopedic management for the physical therapist assistant - Manske, Robert C.; Manske, Robert C. (Elsevier, 2016)
Master the role and the skills of the physical therapist assistant! Fundamental Orthopedic Management for the Physical Therapist Assistant, 4th Edition helps you apply the principles of orthopedic science to physical therapy interventions. First you will learn how to assess flexibility, strength, endurance, and balance, and then you'll become a more valuable PTA by learning the essentials of tissue healing, gait and manual therapy, biomechanics and kinesiology, and the management of orthopedic patients by region and condition. This edition includes a new full-color design and illustrations. --